High-Flow Nasal Cannula versus Non-Invasive Positive Pressure Ventilation in Adults with Acute Hypoxemic (Type 1) Respiratory Failure: A Meta-Analysis of Efficacy, Intubation Rates, and Mortality - Muhammad Reza Arifin; Indra Yovi; Sri Indah Indriani (HM Publisher, 2025)
Background: Acute hypoxemic respiratory failure (AHRF), or Type 1 respiratory failure, is a common life-threatening condition characterized by severe impairment in arterial oxygenation. High-flow nasal cannula (HFNC) and Non-Invasive Positive Pressure Ventilation (NIPPV) are two widely used non-invasive respiratory support strategies. However, their comparative effectiveness in adults with Type 1 AHRF remains a subject of ongoing investigation. This meta-analysis aimed to compare the efficacy, intubation rates, and mortality associated with HFNC versus NIPPV in this patient population. Methods: A systematic search of PubMed, EMBASE, Scopus, and the Cochrane Central Register of Controlled Trials (CENTRAL) was conducted for randomized controlled trials (RCTs) published between January 2014 and December 2024. Studies comparing HFNC with NIPPV in adult patients with Type 1 AHRF were included. The primary outcomes were the rate of endotracheal intubation and all-cause mortality (hospital or 28-day). Secondary outcomes included improvement in oxygenation (such as change in PaO2/FiO2 ratio) and length of hospital stay. Two reviewers independently screened studies, extracted data, and assessed the risk of bias using the Cochrane Risk of Bias tool. Meta-analyses were performed using a random-effects model, and results were expressed as Risk Ratios (RR) with 95% Confidence Intervals (CI) for dichotomous outcomes and Mean Differences (MD) for continuous outcomes. Heterogeneity was assessed using the I² statistic. Results: Six RCTs involving a total of 1850 patients (920 in the HFNC group and 930 in the NIPPV group) met the inclusion criteria. The overall risk of bias in the included studies was moderate. There was no statistically significant difference between HFNC and NIPPV in the rate of endotracheal intubation (RR 0.92, 95% CI 0.75-1.13; I²=28%; 6 studies) or all-cause mortality (RR 0.88, 95% CI 0.69-1.12; I²=15%; 6 studies). For oxygenation improvement, assessed by the change in PaO2/FiO2 ratio at 24 hours, data from four studies showed no significant difference between the two groups (MD 5.8 mmHg, 95% CI -8.5 to 20.1 mmHg; I²=45%). Hospital length of stay was also comparable. Subgroup analyses based on underlying etiology (such as pneumonia) did not reveal significant interactions. Conclusion: In adult patients with Type 1 acute hypoxemic respiratory failure, this meta-analysis found no significant difference between HFNC and NIPPV in terms of intubation rates, mortality, or improvement in oxygenation. Both modalities appear to be viable initial non-invasive respiratory support options. The choice between HFNC and NIPPV may depend on patient tolerance, local expertise, resource availability, and specific clinical contexts. Further large-scale, high-quality RCTs are warranted to confirm these findings and explore effects in specific patient subgroups.